"Tik Tok" Application Impact in English Learning Experience on Motivation and Learning Student Achievement - Nadila Natasya; Adinda Siregar; Angellia Bheriani By; Bambang Nur Alamsyah Lubis (SCHOULID: Indonesian Journal of School Counseling, 2023)
This research aims to find out how the experience of learning English affects students' motivation and learning achievement. This research is descriptive research with a qualitative approach. The data source in this research is the students of SMAS Muhammadiyah 01 Medan whose address is Jalan Utama No. 170, Matsum II City, Medan Area District, Medan City, North Sumatra. The results of this research are that the results of data analysis show that using Tiktok can significantly increase student motivation and learning achievement. Although not all students use Tiktok as a learning medium, they only use Tiktok as entertainment. The average result of the percentage that Tiktok can have a good impact on students' English language skills is 86.7%, where this percentage was obtained from students who felt a good impact from Tiktok. Students think that Tiktok has a good impact on their English language skills. This means that pronunciation, vocabulary, tenses, speaking, reading and writing skills in learning English are increasing and Tiktok can have a good influence as social media if it is applied well by students.